Influence of Structure-modifying Agents in the Synthesis of Zr-doped SBA-15 Silica and Their Use as Catalysts in the Furfural Hydrogenation to Obtain High Value-added Products through the Meerwein-Ponndorf-Verley Reduction - López-Asensio, Raquel; Jiménez-Gómez, Carmen Pilar; García-Sancho, Cristina; Moreno-Tost, Ramón; Cecilia-Buenestado, Juan Antonio; Maireles-Torres, Pedro Jesús (MDPI, 2019)
Zr-doped mesoporous silicas with different textural parameters have been synthesized in the presence of structure-modifying agents, and then characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), N2 adsorption-desorption at -196 ºC, NH3 thermoprogrammed desorption (NH3–TPD), CO2 thermoprogrammed desorption (CO2–TPD), and X-ray photoelectron spectroscopy (XPS). These porous materials were evaluated in the furfural hydrogenation through the Meerwein-Ponndorf-Verley (MPV) reaction. The catalytic results indicate that the catalyst synthesized under hydrothermal conditions and adding a pore expander agent is more active and selective to furfuryl alcohol. However, the Zr-doped porous silica catalysts that were synthesized at room temperature, which possess narrow pore sizes, tend to form i-propyl furfuryland difurfuryl ethers, coming from etherification between furfuryl alcohol (FOL) and isopropanol molecules (used as H-donor) by a SN2 mechanism.
Keywords: Furanos; Biomasa; Hidrogenación; furfural; furfuryl alcohol; catalytic transfer hydrogenation; Zr-SBA-15; biomass; biorefinery